Evaluation of Lakadong turmeric derived curcumin nanogel against resistant biofilms: In-silico, antibacterial and antibiofilm analysis - Sanjib Kumar Sarma, Uloopi Dutta, Bhrigu Kumar Das, Alakesh Bharali, Damiki Laloo, Jun Moni Kalita, Bhanu P. Sahu (Journal of Applied Pharmaceutical Science, 2024)
The emergence of drug resistance can lead to increased mortality and morbidity as treatment efficacy declines, and there is an urgent need to explore novel antibacterial compounds with enhanced effectiveness against drug-resistant bacteria, particularly resistant biofilms. Curcumin, with its antimicrobial activity, can be a potential safe agent; however, studies on its efficacy against resistant biofilm are limited. This study, therefore, aims to explore the potential of curcumin and/or its novel derivatives against a spectrum of resistant biofilm-related pathogens, including bacteria, fungi, and human pathogens. Another study objective is to investigate the effectiveness of the high-yielding Lakadong turmeric (LKD)-derived curcumin for its antibacterial effects and the ability to inhibit biofilm formation in Gram-positive and Gram-negative bacteria using in-vitro assays. A molecular docking study was used to select the most potential binding interaction between the selected protein structure and ligand molecule for the potential efficacy of curcumin against resistant biofilms. Lakadong-derived curcumin-loaded nano gels (LKD-Cur Nanogel) were prepared and tested for antibacterial (zone-inhibition) and biofilm formation (scanning confocal microscope) activity against Staphylococcus aureus and Pseudomonas aeruginosa. Furthermore, Curcumin derivatives were studied in-silico for potential effectiveness against a spectrum of resistant biofilms. The in-silico results showed that curcumin and/or its novel derivatives exhibited high selectivity toward a range of targeted proteins compared to curcumin. Moreover, LKD-Cur Nanogel exhibited significant anti-bacterial activity with an increased mean zone of inhibition compared to positive control. The biofilm formation assay illustrated that LKD-Cur Nanogel effectively disrupted established bacterial biofilms (both for P. aeruginosa and S. aureus) grown on microtiter plates at a concentration of 1,000 μg/ml compared to the control. Therefore, it can be concluded that curcumin and/or its newly modified derivatives could hold promising antibacterial activity targeting diverse biofilm-associated pathogens based on the in-silico and in-vitro study. Moreover, it can be concluded that LKD-derived curcumin nanogels have good antibacterial and antibiofilm efficacy.
Keywords: Lakadong turmeric, curcumin, antimicrobial efficacy, biofilm, in-silico study